Search for neutrino-induced cascades with five years of AMANDA data - Abbasi, R; Abdou, Y; Abu-Zayyad, T; Actis, O; Adams, J; Aguilar, J; Ahlers, M; Andeen, K; Auffenberg, J; Bai, X; Baker, M; Barwick, S; et al. (2011)
We report on the search for electromagnetic and hadronic showers ("cascades") produced by a diffuse flux of extraterrestrial neutrinos in the AMANDA neutrino telescope. Data for this analysis were recorded during 1001 days of detector livetime in the years 2000-2004. The observed event rates are consistent with the background expectation from atmospheric neutrinos and muons. An upper limit is derived for the diffuse flux of neutrinos of all flavors assuming a flavor ratio of νe:νμ: ντ = 1:1:1 at the detection site. The all-flavor flux of neutrinos with an energy spectrum Φ ∝ E-2 is less than 5.0 × 10-7 GeV s-1 sr-1 cm-2 at a 90% C.L. Here, 90% of the simulated signal would fall within the energy range 40 TeV to 9 PeV. We discuss flux limits in the context of several specific models of extraterrestrial and prompt atmospheric neutrino production. © 2010 Elsevier B.V. All rights reserved.